2021
DOI: 10.3390/su13094879
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Protected Strawberry Productions in Central Italy

Abstract: Agricultural activities in Europe cover half of the total area of the continent and are simultaneously a cause of environmental impact and victims of the same impact. Horticultural or fruit crops are considered highly intensive and often employ many crop inputs such as fertilizers, pesticides, and various materials. Strawberry falls into this group, and it has grown in acreage and production more than others globally. The aim of this study is to compare the environmental impact of two strawberry cultivation sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Strawberry (Fragaria × ananassa) is an economically important crop worldwide [1,2]. It has a great nutritional value because it contains minerals, vitamins, flavonoids, and phenolic compounds with beneficial biological properties, for instance antioxidant, anticancer, and anti-inflammatory activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry (Fragaria × ananassa) is an economically important crop worldwide [1,2]. It has a great nutritional value because it contains minerals, vitamins, flavonoids, and phenolic compounds with beneficial biological properties, for instance antioxidant, anticancer, and anti-inflammatory activities [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, [154] reviewing substrates for use in urban farming, found that perlite has the highest environmental impacts because is a material obtained from open-pit mines, which necessitates substantial energy consumption and a lengthy transportation process. Moreover, horticultural and fruit crops are typically regarded as highly intensive and frequently require numerous inputs, including fertilizers, pesticides, and various other materials, and the benefit of one cropping system over another cannot always be established, as was described by [157] in strawberry cultivated in traditional mulched soil tunnel versus a soilless tunnel system, concluding that, in general terms, tunnel exploits more land and crop inputs (excluding pesticides), while the soilless more technology and building materials, thus, making it difficult to establish which system is more environmentally sustainable.…”
Section: Life Cycle Assessment and Eco-friendly Practicesmentioning
confidence: 99%
“…In contrast, large quantities of applied fungicides (i.e., Fosetyl-Al and Imazalil) in orange production in Spain resulted in a 90% contribution to freshwater ecotoxicity [11]. Applied fungicides in fruit production contribute to a small extent to climate change [32,[44][45][46][47][48], terrestrial acidification [32,44,45,47,48], and human toxicity [11,[46][47][48] due to low characterization factors of fungicides for these impacts and other contributing environmental releases. Finally, the only distinction between systemic and contact fungicides can be observed for the contact fungicide mancozeb, which is a key contributor to freshwater ecotoxicity and freshwater eutrophication based on [11,32].…”
Section: Fungicides Contribution To Environmental Impactsmentioning
confidence: 99%